PENGARUH NAFAS DALAM TERHADAP TEKANAN DARAH PADA PASIEN HIPERTENSI - Juwita, Lisavina; Efriza, Ela (REAL in Nursing Journal, 2018)
Hypertension is a condition in which the blood pressure increase. The purpose of this research is to know the effect of deep breathing in response to blood pressure in patients with hypertension. This research used quasi experiment with one group pre test post test. Population this research was 474. The number of samples as many as 10 samples with purposive sampling. The difference in average systolic blood pressure in hypertension patients before and after administering deep breathing techniques was 7,514, with standard deviation 1,190 and value p=0,000 and the difference in avarege diastolic blood pressure on hypertension patiens before and after administering deep breathing techniques was 9,400, with standard deviation 3,748 and value p=0,000. Based on the above it can be concluded that deep breathing can decreased blood pressure in hypertensive patients who were given breath technique in the work-area health center Nilam Sari Bukittinggi City. Expected to apply the techniques of deep breath regularly and choose the peace place. Key words: deep breathing techniques, hypertension, blood pressure.